Transition Pathway Palm Oil Research Framework Toward a Bio-Circular-Green Economy Model Using SWOT Analysis: A Case Study of Thailand - Usapein, Parnuwat; Tuntiwiwattanapun, Nattapong; Polburee, Pirapan; Veerakul, Prakan; Seekao, Chaiyaporn; Chavalparit, Orathai (Frontiers in Environmental Science, 2022)
Climate change, food security, and energy crisis are becoming more intense to our world. Oil palm can be utilized in both the food and biofuel industries. To respond to the crisis, it is necessary to develop palm oil products besides vegetable oil and biodiesel. This paper focuses on the development of strategies to research oil palm throughout the supply chain in Thailand. The SWOT factors (the Strengths, Weaknesses, Opportunities, and Threats) are recognized via interviews stakeholders. These stakeholders are feedstock producers, crude palm oil (CPO) producers, government agencies, biodiesel producers, palm oil refinery producers, and researchers. The results obtained from the data collection were analysed and led to the formulation of strategies for future research on oil palm by TOWS matrix. According to this analysis, future palm oil research framework strategies should be consisted of four categories: (1) oil palm management policy, developing regulation and economic instruments of various forms to systematically manage the oil palm industry, applying big data and smart innovation to analyse market behaviour; (2) oil palm breeding and production technologies, developing smart innovation in line with farmers’ lifestyles, supporting research on oil content analysis and harvesting technology; (3) oil palm biomass conversion technologies, assessing environmental impact through life cycle technology, evaluating the potential reduction of greenhouse gas emissions, increasing the consumption rate of palm biomass; and (4) palm-based oleochemical products, developing oleochemical technology at the industrial level, expanding the potential capacity of producing oleochemical derivative products, increasing the consumption rate and value-added of CPO. All four framework were detailed and revised in line with the information obtained from seminars, comments, and interviews to meet the needs of all stakeholders. This framework will help drive the Bio-Circular-Green economy model (BCG economy model) in the future.